Impact of heavy metals on the quality of the black potato “Solanum Tuberosum” coming from the province of Tarma, Junin, Peru - Borda Luna, Benjamin (2021)
Heavy metals in food are reported as a serious problem due to their toxicity. The study aims to determine the concentration of heavy metals in the black potato Solanum Tuberosum sold in the Ventura Rossi A market, in the district of Rímac, Lima, Peru. The collection of information and the analysis of the metals was carried out from February 04 to 19, 2020. For the study, the heavy metals arsenic (As), cadmium (Cd), copper (Cu), mercury (Hg), molybdenum (Mo), nickel (Ni), lead (Pb) and zinc (Zn) that were analyzed using the EPA method 200.7, Rev.4.4. EMMC / 1994 version, which specifies the determination of metals and trace elements in water and waste by inductive plasma coupled to atomic emission spectrometry, in which results were reported in mean concentration in arsenic (As) of 0.043mg / kg, cadmium (Cd ) 0.036mg / kg, copper (Cu) 0.114mg / kg, mercury (Hg) <0.001mg / kg, molybdenum (Mo) 0.0075mg / kg, nickel (Ni) 0.0145mg / kg, lead ( Pb) of 0.0565 mg / kg and zinc (zn) of 1.138 mg / kg. In addition, for the metals arsenic (As), lead (Pb), mercury (Hg) and cadmium (Cd), values lower than the MPLs established in the FAO Codex Alimentarius were recorded. Also, for copper (Cu) and zinc (Zn), values that comply with the LMPs established in Cuban standard number 493 were recorded. Finally, in Peru, there are no standards that establish maximum limits in foods for direct consumption. that guarantee the food security of the population.